Enabling storage and utilization of low-carbon electricity: power to formic acid. Issue 3 (16th February 2021) - Chatterjee, Sudipta; Dutta, Indranil; Lum, Yanwei; Lai, Zhiping; Huang, Kuo-Wei
Abstract : Power to formic acid via CO2 hydrogenation or electrochemical CO2 reduction has great potential to enable a complete cycle with formic acid to power for the storage and utilization of low-carbon electricity at a scale of multi-gigatonnes per year. Abstract : Formic acid has been proposed as a hydrogen energy carrier because of its many desirable properties, such as low toxicity and flammability, and a high volumetric hydrogen storage capacity of 53 g H2 L −1 under ambient conditions. Compared to liquid hydrogen, formic acid is thus more convenient and safer to store and transport. Converting formic acid to power has been demonstrated in direct formic acid fuel cells and in dehydrogenation reactions to supply hydrogen for polymer electrolyte membrane fuel cells. However, to enable a complete cycle for the storage and utilization of low-carbon or carbon-free electricity, processes for the hydrogenation and electrochemical reduction of carbon dioxide (CO2 ) to formic acid, namely power to formic acid, are needed. In this review, representative homogenous and heterogeneous catalysts for CO2 hydrogenation will be summarized. Apart from catalytic systems for CO2 hydrogenation, a wide range of catalysts, electrodes, and reactor systems for the electrochemical CO2 reduction reaction (eCO2 RR) will be discussed. An analysis for practical applications from the engineering viewpoint will be provided with concluding remarks and an outlook for future challenges and R&D directions.